2008
DOI: 10.1007/s00384-008-0457-5
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in the elderly—surgical treatment and long-term survival

Abstract: The age of patients does not seem to be a prognostic factor for perioperative results; furthermore, the long-term results rather depend on the stage of disease and on adjuvant or palliative treatment, respectively, than on age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 8 publications
6
28
0
3
Order By: Relevance
“…The higher postoperative morbidity rate in the older age patient group is because of the significant enhancement in common postoperative complications. Consistent with our observation, Schiffmann et al also revealed that the worse prognosis was in older CRC patients [24]. Older age may be associated with cardiovascular diseases or other medical illness [26], and with the significantly higher American Society of Anesthesiologists (ASA) classifications [27]; hence, older age is associated with poor overall survival, but not cancer-specific survival, in CRC patients.…”
Section: Discussionsupporting
confidence: 88%
“…The higher postoperative morbidity rate in the older age patient group is because of the significant enhancement in common postoperative complications. Consistent with our observation, Schiffmann et al also revealed that the worse prognosis was in older CRC patients [24]. Older age may be associated with cardiovascular diseases or other medical illness [26], and with the significantly higher American Society of Anesthesiologists (ASA) classifications [27]; hence, older age is associated with poor overall survival, but not cancer-specific survival, in CRC patients.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, data on 5-year cancer-specific survival in the elderly are conflicting. Some studies present similar cancer-specific and diseasefree survival figures in all age groups undergoing curative surgery for colorectal cancer [7,8], while others have found impaired survival in the elderly [9]. These results suggest that elderly patients should be treated with the same surgical strategy as their younger counterparts, at least as long as there is no severe comorbidity.…”
Section: Introductionmentioning
confidence: 88%
“…[6][7][8][9][10] However, the information on tumor features and prognosis for older patients from the developing countries is relatively scarce. In addition, the clinicopathological attributes of this disease in Asian patients are different from the rest of the world.…”
Section: Introductionmentioning
confidence: 99%